1998
DOI: 10.1007/s001250050949
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single doses of pramlintide on gastric emptying of two meals in men with IDDM

Abstract: Gastric emptying is a significant determinant of the blood glucose response after an oral carbohydrate load [1] due to the key role this process plays in regulating the rate of nutrient delivery to the small intestine. Gastric emptying may therefore be a previously under-recognized contributor to variations in glycaemic control in diabetes mellitus. Faster rates of gastric emptying have been reported not only in rat models of insulin-dependent diabetes mellitus (IDDM) [2,3] but also in patients with IDDM [4,5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 25 publications
7
94
2
Order By: Relevance
“…Consistent with preclinical findings of the physiologic role of amylin in postprandial glucose homeostasis (9,10), previous clinical trials in patients with type 1 diabetes have shown that mealtime amylin replacement with pramlintide slows the rate of nutrient delivery from the stomach to the small intestine (15,16) and prevents an abnormal increase in glucagonemia after meals (17,18). Collectively, these effects result in a marked improvement in postprandial glycemic excursions compared with prandial injections of insulin alone (17,19).…”
Section: Open-label Extension (Weeks 52-104)mentioning
confidence: 56%
See 1 more Smart Citation
“…Consistent with preclinical findings of the physiologic role of amylin in postprandial glucose homeostasis (9,10), previous clinical trials in patients with type 1 diabetes have shown that mealtime amylin replacement with pramlintide slows the rate of nutrient delivery from the stomach to the small intestine (15,16) and prevents an abnormal increase in glucagonemia after meals (17,18). Collectively, these effects result in a marked improvement in postprandial glycemic excursions compared with prandial injections of insulin alone (17,19).…”
Section: Open-label Extension (Weeks 52-104)mentioning
confidence: 56%
“…First, a slowing of the rate of nutrient delivery from the stomach to the small intestine was demonstrated (15,16). Second, prevention of an abnormal postprandial increase in plasma glucagon was demonstrated (17,18).…”
mentioning
confidence: 99%
“…Healthy subjects were studied on two occasions (euglycemia and hyperglycemia), and type 1 diabetic subjects were studied on three occasions (euglycemia and hyperglycemia with and without 30 g pramlintide [Amylin Pharmaceuticals, San Diego, CA], injected subcutaneously in the lower abdominal wall with the meal, which was designed to replace absent IAPP secretion as indicated by its effects on gastric emptying compared with hyperglycemia in healthy subjects estimated from previous studies [13,14]). Healthy subjects received only placebo injections.…”
Section: Protocolmentioning
confidence: 99%
“…Pramlintide has multiple mechanisms of action [16][17][18] that decrease postprandial glycemia, resulting in improved glycemic control with less insulin and the potential for weight loss.…”
mentioning
confidence: 99%